1999
DOI: 10.1121/1.424610
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear saturation of thermoacoustic instability

Abstract: In earlier work [Watanabe et al., J. Acoust. Soc. Am. 102, 3484–3496 (1997)] a quasi-one-dimensional nonlinear model for thermoacoustic devices was developed. The model reduces exactly to the well-known Rott theory upon linearization, but numerical work has shown that it is also able to predict nonlinear features in agreement with experiment. In this work, a weakly nonlinear analysis of the model is carried out for conditions close to the linear stability threshold. The level at which the amplitude of the line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Multiple authors (Swift 1992;Karpov & Prosperetti 2000;Hamilton et al 2002;Penelet et al 2005) have discussed the higher harmonic generation in non-combustiondriven thermoacoustically unstable waves, restricting their analysis to only a first few overtones of the unstable mode. Biwa et al (2011) reported the first experimental observation of energy cascade in thermoacoustically sustained shock waves in a looped thermoacoustic resonator.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple authors (Swift 1992;Karpov & Prosperetti 2000;Hamilton et al 2002;Penelet et al 2005) have discussed the higher harmonic generation in non-combustiondriven thermoacoustically unstable waves, restricting their analysis to only a first few overtones of the unstable mode. Biwa et al (2011) reported the first experimental observation of energy cascade in thermoacoustically sustained shock waves in a looped thermoacoustic resonator.…”
Section: Introductionmentioning
confidence: 99%
“…where p ref is the reference pressure (which is set when the system is initially filled with gas), and T ref is the reference temperature. Equation (35) guarantees that the total mass in the system is conserved. The necessity of this replacement is explained in Appendix A.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…For a finite volume scheme, we replace one local DC continuity equation with Eq. (35). Since closed thermoacoustic systems are often filled at room temperature, a beneficial effect of this global equation is the fact that we obtain the DC pressure increase in the system under operating conditions.…”
Section: Appendix A: Mass Balancementioning
confidence: 99%
See 1 more Smart Citation
“…For the study of the standing wave thermoacoustic engines functioning in the start mode Karpov et.al. [2] applied a weakly non-linear theory of the thermoacoustic instability in a channel with temperature gradient. The motivation for this work was provided by the research results of the lumped thermal capacity model presented by Matveev [3].…”
Section: Introductionmentioning
confidence: 99%